2017
DOI: 10.1007/s10853-017-0969-x
|View full text |Cite
|
Sign up to set email alerts
|

A facile way to produce epoxy nanocomposites having excellent thermal conductivity with low contents of reduced graphene oxide

Abstract: A well-dispersed phase of exfoliated graphene oxide (GO) nanosheets was initially prepared in water. This was concentrated by centrifugation and was mixed with a liquid epoxy resin. The remaining water was removed by evaporation, leaving a GO dispersion in epoxy resin. A stoichiometric amount of an anhydride curing agent was added to this epoxy-resin mixture containing the GO nanosheets, which was then cured at 90°C for 1 h followed by 160°C for 2 h. A second thermal treatment step of 200°C for 30 min was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 52 publications
7
36
0
Order By: Relevance
“…In agreement with known concensus [43] the epoxy nano-composites here are seen to have a two-step degradationbetween 350 o C -450 o C of the epoxy groups and 450 o C -485 700 o C due to char formation from the thermal degradation of the epoxy and the fillers. In the Sial T-403 cured epoxies, the onset of degradation temperature (Td, o C, at 5% weight loss, Figure 11-12 ) is seen to drop slightly by ~2-4 o C at lower GO contents before finally showing an increment of ~4 o C at 0.50wt%.…”
Section: Thermo Gravimetric Analysis (Tga)supporting
confidence: 86%
See 2 more Smart Citations
“…In agreement with known concensus [43] the epoxy nano-composites here are seen to have a two-step degradationbetween 350 o C -450 o C of the epoxy groups and 450 o C -485 700 o C due to char formation from the thermal degradation of the epoxy and the fillers. In the Sial T-403 cured epoxies, the onset of degradation temperature (Td, o C, at 5% weight loss, Figure 11-12 ) is seen to drop slightly by ~2-4 o C at lower GO contents before finally showing an increment of ~4 o C at 0.50wt%.…”
Section: Thermo Gravimetric Analysis (Tga)supporting
confidence: 86%
“…In the Sial T-403 cured epoxies, the onset of degradation temperature (Td, o C, at 5% weight loss, Figure 11-12 ) is seen to drop slightly by ~2-4 o C at lower GO contents before finally showing an increment of ~4 o C at 0.50wt%. The reduction of Td in GO filled system have already been observed and is suspected to be due to the easier thermal decomposition of the oxygen con-490 taining functionalities (OCFs) of the filler [43]. On the other hand, adding GO-ButA to the epoxy is seen to increase Td by ~15-30 o C (Figure 11, Table 2).…”
Section: Thermo Gravimetric Analysis (Tga)mentioning
confidence: 84%
See 1 more Smart Citation
“…Shape, filler dispersion and interfacial adhesion to the epoxy matrix are the crucial deciding factors for the mechanical characterization. As filler percentage is increased, particles get aggregated easily due to high specific surface area and stronger Van Der Waals forces between adjacent particles [8]. Further, filler packing density and non-uniform dispersion at higher filler concentrations create voids and weaken the bonding between filler and matrix which results in ineffective load transfer between matrix and filler, thereby fractures easily at lower loads [31].…”
Section: Surface Potential Measurements Under DC Voltagementioning
confidence: 99%
“…Earlier studies revealed that the improvement in tensile behaviour of epoxy nanocomposite materials merely depends on the efficient filler dispersion and the interfacial adhesion between filler and the matrix [8][9][10]. The polymer nanocomposite materials with conductive fillers find their applications include embedded capacitance material (ECM), high energy density capacitors, and electromagnetic interference (EMI) shielding material in electronic circuits [5].…”
Section: Introductionmentioning
confidence: 99%